Efficient genome editing in Claviceps purpurea using a CRISPR/Cas9 ribonucleoprotein method - Lu Yu; Meili Xiao; Zhihua Zhu; Yinmei Wang; Zhihua Zhou; Pingping Wang; Gen Zou (Synthetic and Systems Biotechnology, 2022)
Claviceps purpurea produces many pharmacologically important ergot alkaloids (EAS), which are widely used to treat migraine and hypertension and to aid childbirth. Although an EAS biosynthetic cluster of C. purpurea has been discovered more than 20 years ago, the complete biosynthetic pathway of EAS has not been fully characterized until now. The main obstacle to elucidating this pathway and strain modification is the lack of efficient genome-editing tools for C. purpurea. The conventional gene manipulation method for C. purpurea relies on homologous recombination (HR), although the efficiency of HR in C. purpurea is very low (∼1–5%). Consequently, the disruption of target genes is laborious and time-consuming. Although CRISPR/Cas9 genome-editing methods based on in vivo Cas9 expression and gRNA transcription have been reported recently, their gene-disruption efficiency is still very low. Here, we developed an efficient genome-editing system in C. purpurea based on in vitro assembled CRISPR/Cas9 gRNA ribonucleoprotein complexes. As proof of principle, three target genes were efficiently knocked out using this CRISPR/Cas9 ribonucleoprotein complex-mediated HR system, with editing efficiencies ranging from 50% to 100%. Inactivation of the three genes, which are closely related to uridine biosynthesis (ura5), hypha morphology (rac), and EAS production (easA), resulted in a uridine auxotrophic mutant, a mutant with a drastically different phenotype in axenic culture, and a mutant that did not produce EAS, respectively. Our ribonucleoprotein-based genome-editing system has a great advantage over conventional and in vivo CRISPR/Cas9 methods for genome editing in C. purpurea, which will greatly facilitate elucidation of the EAS biosynthetic pathway and other future basic and applied research on C. purpurea.